VALIDASI METODE PENENTUAN Cd (II) DALAM PUPUK NPK SECARA SPEKTROFOTOMETRI SERAPAN ATOM NYALA DI LABORATORIUM UJI KUALITAS, PT. PUPUK KALIMANTAN TIMUR - Leonardus Lewo Hayon; Alimuddin Alimuddin; Aman Sentosa Panggabean (JURNAL KIMIA MULAWARMAN, 2021)
The research about validation method of determination of Cd (II) in NPK fertilizer by Flame Atomic Absorption Spectrophotometry at the Quality Control Laboratory, PT. Pupuk Kaltim has been done. Determination of Cd (II) was done by referring to the Indonesian National Standard (SNI) 2803:2012. Based on the research results obtained by the correlation coefficient (r) was 0.9991; reproducibility with a relative standard deviation (RSD) value was 4.502 % less than 2/3 CV Horwitz was 9.757 and repeatability with a relative standard deviation (RSD) value was 5.225% less than 2/3 CV Horwitz was 9.695; % recovery was in the range of 80-110 % with an average was 98.56 %; limit of detection was 0.056 mg/kg and limit of quantitation was 0,066 mg/kg; uncertainty estimation of measurement with uncertainty components of concentration, volume, mass, precision and purity of the standard solution, obtained the expanded uncertainty value with a 95 % confidence level was Â± 0.197 mg/kg and uncertainty percentage value was 10.43 %.